ANALISIS KANDUNGAN PLASTIK PADA GORENGAN DI KAWASAN PERGURUAN TINGGI KOTA PADANG - Sari, Milya; Roza, Media; Nurhasanah, Nurhasanah (IAIN Batusangkar, 2017)
Nowadays, there are many foods that contain harmful substances in the community. Among them are fried foods that contain plastic. Similar cases were also found in the campus area in city of Padang. Based on preliminary observations it was found that some fried foods sold in one campus area in the city of Padang were indicated to contain plastic. This study therefore aims to determine whether fried foods sold in the city of Padang contained plastic, what the physical characteristics of fried foods that contain plastic were, and what plastic content contained in the cooking oil. This type of research was descriptive qualitative. Sampling in this study was conducted by purposive sampling in 16 locations around the campus area in the city of Padang. The data of the research data were obtained from physical and chemical sample identifications. Physical identification included data on shape, color, fragility, and fuel test. Physically indicated samples containing plastic then analyzed chemically with GC-MS. The results of the study showed that the physical characteristics of fried foods that contain plastic were black clots when observed with a microscope, there are white patches on the surface of the fried, brittle for hours, and if it was burned, it burnt and produced melt. The results of the chemical analysis showed that from 16 sampling points 11 samples (68.75%) positive contained plastic. The type of plastic compound found was from PVC (Polyvinyl chloride).